Asymmetric light transmission based on coupling between photonic crystal waveguides and L1/L3 cavity. Issue 16 (8th September 2017) - Zhang, Jinqiannan; Chai, Hongyu; Yu, Zhongyuan; Cheng, Xiang; Ye, Han; Liu, Yumin
Abstract: A compact design of all-optical diode with mode conversion function based on a two-dimensional photonic crystal waveguide and an L1 or L3 cavity is theoretically investigated. The proposed photonic crystal structures comprise a triangular arrangement of air holes embedded in a silicon substrate. Asymmetric light propagation is achieved via the spatial mode match/mismatch in the coupling region. The simulations show that at each cavity's resonance frequency, the transmission efficiency of the structure with the L1 and L3 cavities reach 79% and 73%, while the corresponding unidirectionalities are 46 and 37 dB, respectively. The functional frequency can be controlled by simply adjusting the radii of specific air holes in the L1 and L3 cavities. The proposed structure can be used as a frequency filter, a beam splitter and has potential applications in all-optical integrated circuits.